Microbial communities are thermally more sensitive in warm-climate lizards compared with their cold-climate counterparts - Zhu, Xia-Ming; Chen, Jun-Qiong; Du, Yu; Lin, Chi-Xian; Qu, Yan-Fu; Lin, Long-Hui; Ji, Xiang (Frontiers in Microbiology, 2024)
Environmental temperature affects the composition, structure, and function of the gut microbial communities in host animals. To elucidate the role of gut microbiota in thermal adaptation, we designed a 2 species  3 temperatures experiment, whereby we acclimated adult males of two agamid lizard species (warm-climate Leiolepis reevesii and cold-climate Phrynocephalus przewalskii) to 20, 28, and 36 °C for two weeks and then collected their fecal and small-intestinal samples to analyze and compare the microbiota using 16S rRNA gene amplicon sequencing technology. The fecal microbiota displayed more pronounced interspecific differences in microbial community than the small-intestinal microbiota in the two species occurring in thermally different regions. The response of fecal and small-intestinal microbiota to temperature increase or decrease differed between the two species, with more bacterial taxa affected by acclimation temperature in L. reevesii than in P. przewalskii. Both species, the warm-climate species in particular, could cope with temperature change by adjusting the relative abundance of functional categories associated with metabolism and environmental information processing. Functional genes associated with carbohydrate metabolism were enhanced in P. przewalskii, suggesting the contribution of the fecal microbiota to cold-climate adaptation in P. przewalskii. Taken together, our results validate the two hypotheses tested, of which one suggests that the gut microbiota should help lizards adapt to thermal environments in which they live, and the other suggests that microbial communities should be thermally more sensitive in warm-climate lizards than in cold-climate lizards.